2011
DOI: 10.1111/j.1399-5618.2011.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

An online survey of tobacco use, intentions to quit, and cessation strategies among people living with bipolar disorder

Abstract: Objectives Tobacco use is prevalent among people living with bipolar disorder. We examined tobacco use, quit attempts, and tobacco-related attitudes and intentions among 685 individuals with bipolar disorder who smoked ≥ 100 cigarettes in their lifetime. Methods Data were collected online through the website of the Depression and Bipolar Support Alliance a mood disorder peer-support network. Results The sample was 67% female, 67% aged 26 to 50, and 89% Caucasian; 87% were current smokers; 92% of current sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 37 publications
(26 reference statements)
3
42
1
4
Order By: Relevance
“…Indeed, UK clinical guidelines on smoking cessation in secondary care advise that all health and social care practitioners in in‐patient and community‐based mental health services identify smokers and offer advice and assistance to quit 11. However, smokers with mental illness are less likely to be offered advice and support to quit than those without 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, UK clinical guidelines on smoking cessation in secondary care advise that all health and social care practitioners in in‐patient and community‐based mental health services identify smokers and offer advice and assistance to quit 11. However, smokers with mental illness are less likely to be offered advice and support to quit than those without 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…They also have a higher smoking prevalence, greater level of nicotine dependence, lower smoking cessation rates, and disproportionate health and financial burdens from smoking (Williams, Steinberg, Griffith, & Cooperman, 2013). Considerable evidence suggests that adults with mental illnesses are seldom offered smoking cessation treatment by service providers (Himelhoch & Daumit, 2003;Prochaska et al, 2011; Substance Abuse and Mental Health Services Administration, 2014a) and remain unaware that effective, evidence-based interventions are available (Christiansen et al, 2016). Coupled with this, little is known about the factors associated with current smoking in this population that impede efforts to design smoking cessation interventions that address its special needs and circumstances.…”
mentioning
confidence: 98%
“…11 Several studies have reported equal interest in quitting among smokers with SMI relative to the general population, [12][13][14] and a few studies have examined interest in or use of cessation medications. In an online survey, 78% of 685 smokers with bipolar disorder expressed a desire to use cessation pharmacotherapy to quit smoking, 15 and in two treatment studies with psychiatric outpatients interested in quitting, over 80% of participants randomised to intervention used study-provided 16 and clinic-provided 17 NRT. In a treatment study in which desire to quit was not required to enrol, 34% of depressed outpatients entered cessation treatment that included a behavioural component plus NRT.…”
mentioning
confidence: 99%